PEMBERDAYAAN INDUSTRI KECIL MENENGAH (IKM) MELALUI PELATIHAN DAN BIMBINGAN OLAHAN PRODUK MAKANAN BERBASIS PALA DI UPTD SENTRA IKM PALA ACEH SELATAN - Uswatun Hasanah; Irvan Subandar; Sanusi Sanusi; Rivansyah Suhendra; Darwin Hendri (Lembaga Penelitian dan Pengabdian Masyarakat, 2023)
Nutmeg is one of the most popular export commodities in the world. Starting from seeds, mace, and nutmeg oil, they are targeted in the pharmaceutical, perfume and cosmetic industries as well as the food and beverage industry. However, it is still rare for nutmeg skin to be used and processed into a product of economic value. In society, a lot of nutmeg meat is thrown away and becomes waste. The IKM empowerment program at the Nutmeg IKM center aims to develop the knowledge and skills of nutmeg business actors in the South Aceh IKM Center to process nutmeg waste into value-added food products. This program promotes the manufacture of dodol made from nutmeg or called Dodol Pala. The program implementation method is divided into three stages: (1) Preparation, designing activities and coordinating with the South Aceh Nutmeg IKM Sentra UPTD; (2) Implementation of guidance, namely developing the knowledge of business actors about processed products made from nutmeg and (3) Training and mentoring, training activities with direct practice of making nutmeg dodol. Assistance is focused on making product packaging and marketing. This training involved various parties, including members of the Teuku Umar University Higher Education, South Aceh Nutmeg IKM Sentra UPTD, nutmeg business actors (IKM), and students. The achievement of this activity, the participants succeeded in developing knowledge about the benefits of nutmeg assessed from their participation during the three days following the activity. In addition, the participants also succeeded in making good quality nutmeg dodol. This activity is expected to be a motivation for nutmeg business actors in South Aceh district to implement their knowledge after this activity.